Penerapan Nilai-Nilai Kebijaksanaan Lokal dalam Pembelajaran Ilmu Sosial untuk Menguatkan Karakter Siswa Sekolah Menengah Pertama. - Astuti, Sri; Muhammad Mona Adha, Muhammad; Apri Wahyudi, Apri; Irma Lusi Nugraheni, Irma Lusi Nugraheni; Pujiati, Pujiati (UNDIKMA, 2026)
This study aims to analyze the contribution of the integration of local wisdom values in learning Social Studies (IPS) towards strengthening the character of Junior High School (SMP) students. In the midst of globalization and rapid technological development, local cultural values are often marginalized, even though they contain great potential in the formation of national character and identity. Through a Systematic Literature Review (SLR) approach with thematic analysis of various studies from 2017-2025, this study found that the integration of local wisdom in social studies learning is able to instill values of mutual cooperation, tolerance, responsibility, and love for the country. The strategies used include contextual learning, local culture-based projects, and the development of teaching media relevant to the lives of surrounding communities. The role of the teacher is a key factor in internalizing these values through exemplary, collaboration with the community, and the application of the principles of the Pancasila Student Profile. The results also show that local wisdom-based learning increases student engagement, strengthens cultural identity, and encourages the formation of strong social and moral character. Thus, the integration of local cultural values in social studies learning not only functions as cultural preservation, but also as an effective strategy in shaping a young generation with character, noble character, and global competitiveness